Misconceptions about HIV infection in Kinshasa (Democratic Republic of Congo): a case–control study on knowledge, attitudes and practices. (21st November 2014) - Carlos, Silvia; Martínez-González, Miguel Ángel; Burgueño, Eduardo; López-del Burgo, Cristina; Ruíz-Canela, Miguel; Ndarabu, Adolphe; Tshilolo, Léon; Tshiswaka, Philomène; Labarga, Pablo; de Irala, Jokin
Abstract : Objectives: To evaluate the prevalence of HIV-related misconceptions in an outpatient centre of Kinshasa (Democratic Republic of Congo) and analyse the association between these beliefs and HIV infection. Methods: A case–control study was carried out from December 2010 until June 2012. We assessed 1630 participants aged 15–49 attending a primary outpatient centre in Kinshasa: 762 HIV Voluntary Counselling and Testing attendees and 868 blood donors. A 59-item questionnaire about knowledge, attitudes and practice was administered during a face-to-face interview, followed by an HIV test. Cases and controls were respondents with a newly diagnosed HIV-positive or HIV-negative test, respectively. Unconditional logistic regression was used to analyse the association between misconceptions and HIV seropositivity. Results: 274 cases and 1340 controls were recruited. Cases were more likely than controls to have a low socioeconomic status, no education, to be divorced/separated or widowed. An association was found between the following variables and HIV seropositivity: having a poor HIV knowledge (adjusted OR=2.79; 95% CI 1.43 to 5.45), not knowing a virus is the cause of AIDS (adjusted OR=2.03; 95% CI 1.38 to 2.98) and reporting more than three HIV-transmission-related misconceptions (adjusted OR=3.30; 95% CI 1.64 to 6.64), such as thinking an HIV-positive person cannot look healthy and that HIV is transmitted by sorcery, God's punishment, a kiss on the mouth, mosquitoes, coughs/sneezes or undercooked food. Conclusions: Despite having access to healthcare services, there are still many people in Kinshasa that have HIV-related misconceptions that increase their HIV risk. Our findings underscore the need for a culturally adapted and gender-orientated basic HIV information into Congolese HIV prevention programmes.